Estrutura e variação espacial da ictiofauna em um reservatório do semiárido brasileiro - Freire, Carlos Eduardo Campos (2013)
The objective of this paper was to study the spacial structure of the assembly of fish in a reservoir of the Brazilian semibarren. Quarterly collections had been made during two years, in the three regions of the reservoir Santa Cruz's Apodi, Brazilian Semiarid (lacustrine, transition and fluvial ) using gill nets and the captured individuals had been separated by species, counted and the abundance transformed into CPUE for the analyses. The wealth has been calculated estimated by the Jacknife method, index of diversity of Shannon-Winner and equitability. To evaluate the spacial distribution of the assembly we use ordinance MDS (Bray-Curtis distance). ANOSIM was applied to verify statistical differences (p<0,05) in the spacial structure of the assemblies between the regions and SIMPER was used to identify the species that contribute most for the dissimilarity in captures by region. 6,047 individuals of 20 species, 10 families and 3 orders had been captured: Characiformes, Siluriformes and Perciformes. The biggest wealth of species was estimated in the fluvial region (21.8±1.5). The biggest values of diversity (H' =2.878) and equitability (J' =0.7150) had been found in the lacustrine and transistion regions. In accordance with the analyses of MDS and ANOSIM, different assemblies had been found in the reservoir with significant difference between the fluvial region and the lacustrine and transistion regions. The Analysis SIMPER identified Moenkausia dichroura as the species that contributed the most for the difference between the regions of the reservoir. Our results had indicated that the spacial structure of the assembly of fish of the reservoir of Santa Cruz differed from Brazilian reservoirs located in other climatic regions. The intermittency characteristics of the river and the reservoir limnological aspects were the major discriminators of results for the patterns of diversity and spatial distribution of fish species found in the study